A Pterin-Dependent Signaling Pathway Regulates a Dual-Function Diguanylate Cyclase-Phosphodiesterase Controlling Surface Attachment in Agrobacterium tumefaciens - Nathan Feirer (American Society for Microbiology, 2015)
ABSTRACT The motile-to-sessile transition is an important lifestyle switch in diverse bacteria and is often regulated by the intracellular second messenger cyclic diguanylate monophosphate (c-di-GMP). In general, high c-di-GMP concentrations promote attachment to surfaces, whereas cells with low levels of signal remain motile. In the plant pathogen Agrobacterium tumefaciens, c-di-GMP controls attachment and biofilm formation via regulation of a unipolar polysaccharide (UPP) adhesin. The levels of c-di-GMP in A. tumefaciens are controlled in part by the dual-function diguanylate cyclase-phosphodiesterase (DGC-PDE) protein DcpA. In this study, we report that DcpA possesses both c-di-GMP synthesizing and degrading activities in heterologous and native genetic backgrounds, a binary capability that is unusual among GGDEF-EAL domain-containing proteins. DcpA activity is modulated by a pteridine reductase called PruA, with DcpA acting as a PDE in the presence of PruA and a DGC in its absence. PruA enzymatic activity is required for the control of DcpA and through this control, attachment and biofilm formation. Intracellular pterin analysis demonstrates that PruA is responsible for the production of a novel pterin species. In addition, the control of DcpA activity also requires PruR, a protein encoded directly upstream of DcpA with a predicted molybdopterin-binding domain. PruR is hypothesized to be a potential signaling intermediate between PruA and DcpA through an as-yet-unidentified mechanism. This study provides the first prokaryotic example of a pterin-mediated signaling pathway and a new model for the regulation of dual-function DGC-PDE proteins. IMPORTANCE Pathogenic bacteria often attach to surfaces and form multicellular communities called biofilms. Biofilms are inherently resilient and can be difficult to treat, resisting common antimicrobials. Understanding how bacterial cells transition to the biofilm lifestyle is essential in developing new therapeutic strategies. We have characterized a novel signaling pathway that plays a dominant role in the regulation of biofilm formation in the model pathogen Agrobacterium tumefaciens. This control pathway involves small metabolites called pterins, well studied in eukaryotes, but this is the first example of pterin-dependent signaling in bacteria. The described pathway controls levels of an important intracellular second messenger (cyclic diguanylate monophosphate) that regulates key bacterial processes such as biofilm formation, motility, and virulence. Pterins control the balance of activity for an enzyme that both synthesizes and degrades the second messenger. These findings reveal a complex, multistep pathway that modulates this enzyme, possibly identifying new targets for antibacterial intervention.